Formation of the student civic position at the present stage of society development - Tatiana A. Miroshina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Democratic principles and values must be learned by every generation in order to solve pressing problems. The purpose of this study was to theoretically substantiate and experimentally test the pedagogical conditions for the formation of the civic position of students at higher educational institution. The object of research is the civic position of students. We have created and tested pedagogical conditions in experimental work. The sample consisted of 90 teachers, including 22 curators, 260 students of the Kuzbass State Agricultural Academy. The survey was carried out from 2016 to 2020. The paper presents the results of the pedagogical experiment, confirmed by the data of a comprehensive assessment of the formation level of the student civic position at the present stage of society development. The substantive component of the activities of teachers, students in classroom and extracurricular activities, based on the principles of citizenship, democracy, tolerance, involvement in the experience of civic action is considered. The course of organizing the activities of curators on the formation of student civic position, the development of self-government in student groups is presented. The work of the academy on the development of partnerships with the public, educational institutions, government, and business is described. Analysis of the results allows us to state that this process is controlled. The pedagogical conditions are: interaction of all subjects of the academy in classroom and extracurricular activities, their professional training, interaction with the public; the formation of temporary working teams from teachers to highlight special topics in the disciplines studied by students, issues that affect the development of student civic consciousness and behavior and the widespread use of active teaching methods in the educational process; organization of curators activities aimed at the formation of student civic position; monitoring the process of student civic position formation.